Increasing Farmer Productivity with Clove Shelling Tools Dulamayo Puncak Farmers Group - Abidin, Zainal; Tamrin, Moh Muhrim; Sudiarta, I Made; Syamsir, Syamsir; Jafar, Muh Iqbal; Jafar, Isran; Hasan, Fardyansjah (Jurnal Pengabdian Masyarakat, 2024)
Purpose: The project aimed to improve clove farming in Dulamayo Selatan village, Telaga Subdistrict, Gorontalo District, which is one of the clove-producing villages in Gorontalo Province. The team designed clove shelling technology to help farmers shell (separate the stalk and flower) their clove harvests. Method: The initial activity of the project was to conduct a Focus Group Discussion (FGD) or discussion with the farmer group partners. Training on making organic fertilizer (compost) was carried out, utilizing materials around which can then be applied to clove plants. The design of the clove shelling tool was carried out by the team along with the students involved. Practical Applications: The clove shelling tool has been handed over to the farmer group, a total of 5 tools. Through the introduction of clove shelling technology and training in making organic fertilizers, farmers’ knowledge related to technology adoption and understanding in clove farming efforts through counseling and simulation has increased. Conclusion: The project successfully introduced a new technology for clove shelling and provided training for making organic fertilizer. This has not only eased the process of clove farming but also increased the knowledge of farmers about technology adoption and understanding in clove farming efforts